(Re)Framing a problem: Militancy in question - Sales, André Luis Leite De FigueirêDo [UNESP]; Fontes, Flávio Fernandes; Yasui, Silvio [UNESP] (Associacao Brasileira de Psicologia, 2018)
Even though “militancy” is frequently used in scientific literature and in the daily life of parties and social movements, there are few definitions of the term. Our goal is to convert the idea of militancy into a research problem. A Brazilian scientific literature review shows that the term is used either as an adjective, either as a noun. We conceptualize militancy as a methodology to produce collective action aiming to intervene, or to interfere, in current social norms. This methodology focuses on organizations such as parties and unions, characterized by strict discipline that aims to produce docility, commitment, and obeisance. Then, we show how New Social Movements (NSM) have created unconventional tactics and organizations, offering an alternative to the militant methodology. Organizing teams using horizontal arrangements, operating with decentralized and autonomous networks, recognizing the diversity of its participants, NSM are occupying the streets and reinventing the repertoires of collective action and protest. We suggest the use of the word “activism” to describe this methodology. By distinguishing militancy from activism we wish to re(frame) some problems in the Brazilian scene of political engagement and protest.
Keywords: Activism; Militancy; Social movements; Subjectivity